2022
DOI: 10.3389/fpls.2022.1050104
|View full text |Cite
|
Sign up to set email alerts
|

AMF colonization affects allelopathic effects of Zea mays L. root exudates and community structure of rhizosphere bacteria

Abstract: Arbuscular mycorrhizal fungi (AMF) widely exist in the soil ecosystem. It has been confirmed that AMF can affect the root exudates of the host, but the chain reaction effect of changes in the root exudates has not been reported much. The change of soil microorganisms and soil enzyme vigor is a direct response to the change in the soil environment. Root exudates are an important carbon source for soil microorganisms. AMF colonization affects root exudates, which is bound to have a certain impact on soil microor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…This is in line with previous findings [11,21] that AMF inoculation enhances vegetative development through improved water and nutrient uptake. Sb treatment impact negatively AMF colonization, including reduction in hyphal length, and arbuscules number (Table 1), which was consistent with existing literature on the detrimental effects of heavy metals on AMF growth, mostly through inhibiting the germination of spores and preventing them to infect a suitable host root and or through disrupting colonization process after host contact [22] . In the present study, the reduction in maize roots AMF colonization for plants treated with Sb, was 51% higher (Table 1) than the slight reduction reported by Hao et al (2021) [14] and Zhang et al (2019) [1] when treated with La and Cd, indicating a likely higher sensitivity of AMF to Sb toxicity.…”
Section: Sb-treatment Inhibits Amf Colonization Growth and Nutriment ...supporting
confidence: 89%
“…This is in line with previous findings [11,21] that AMF inoculation enhances vegetative development through improved water and nutrient uptake. Sb treatment impact negatively AMF colonization, including reduction in hyphal length, and arbuscules number (Table 1), which was consistent with existing literature on the detrimental effects of heavy metals on AMF growth, mostly through inhibiting the germination of spores and preventing them to infect a suitable host root and or through disrupting colonization process after host contact [22] . In the present study, the reduction in maize roots AMF colonization for plants treated with Sb, was 51% higher (Table 1) than the slight reduction reported by Hao et al (2021) [14] and Zhang et al (2019) [1] when treated with La and Cd, indicating a likely higher sensitivity of AMF to Sb toxicity.…”
Section: Sb-treatment Inhibits Amf Colonization Growth and Nutriment ...supporting
confidence: 89%
“…Consequently, different microbial groups are subject to varying degrees of inhibition or promotion. Notably, no signi cant distinctions were observed in the microbial content between the rhizosphere and non-rhizosphere soil of the same plant species (Ma et al, 2022;Zhang, N. et al, 2022;Zhang et al, 2021). This can be attributed to the fact that these plant populations exhibit characteristics of r-selected organisms, characterized by high birth rates, small individual sizes, strong dispersal capabilities, and adaptability to changing habitats.…”
Section: The Taxonomic Composition Of Microbial Communitiesmentioning
confidence: 94%
“…In the study conducted by Ma et al, the measurement and analysis of root exudates and allelopathic effects of maize were carried out following colonization by arbuscular mycorrhizal fungi (AMF) [18]. Furthermore, the enzymatic robustness and microbial variety of maize rhizosphere soil were also assessed.…”
Section: The Impact Of Amf Colonization On Plant Disease Resistancementioning
confidence: 99%
“…Allelopathy is the term used to describe the capability of plants to produce chemicals that hinder the growth of neighboring plants. This decrease in allelopathic effects implies that AMF colonization may augment plant growth by reducing competition from neighboring plants [18] [Table 1]. Moreover, the study revealed that AMF colonization led to heightened enzymatic activities in the rhizosphere soil.…”
Section: The Impact Of Amf Colonization On Plant Disease Resistancementioning
confidence: 99%